Design and development of multi-transceiver lorafi board consisting LoRa and ESP8266-wifi communication module - Azmi, N.; Sudin, S.; Kamarudin, L.M.; Zakaria, A.; Visvanathan, R.; Cheik, G.C.; Zakaria, S.M.M.S; Alfarhan, K.A.; Ahmad, R.B. (2018)
The advancement of Micro-Electro-Mechanical-Systems (MEMS), microcontroller technologies and the idea of Internet of Things (IoT) motivates the development of wireless modules (e.g. WiFi, Bluetooth, Zigbee, and LoRa) that are small and affordable. This paper aims to provide detailed information on the development of the LoRaFi board. The LoRaFi 1.0 is a multi-protocol communication board developed by Centre of Excellence for Advanced Sensor Technology (CEASTech). The board was developed for but not limited to monitor the indoor air quality. The board comprises two different wireless communication modules namely, Long-range technology (LoRa) and WiFi (using ESP8266). The board can be configured to communicate either using LoRa or WiFi or both. The board has been tested and the wireless communication operates successfully. Apart from LoRa, WiFi enables data to be forwarded to the cloud/server where the data can be stored for further data analysis. This helps provide users with real-time information on their smartphones or other applications. In the future, researchers will conduct tests to investigate the communication link quality. Newer version with reduced board size and additional wireless communication module will be developed in the future as to increase board flexibility and widen the range of applications that can use the board.